Profesjonalizacja marketingowego zarządzania w klubach sportowych na rynkach lokalnych = The professionalization of marketing management in sports club in the local market - Sławomir Kowalski (Kazimierz Wielki University, 2015)
Kowalski Sławomir. Profesjonalizacja marketingowego zarządzania w klubach sportowych na rynkach lokalnych = The professionalization of marketing management in sports club in the local market. Journal of Education, Health and Sport. 2015;5(11):481-491. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35681 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A481-491 http://pbn.nauka.gov.pl/works/684731 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Original Text published © The Author (s) 2015. Kowalski Sławomir. Profesjonalizacja marketingowego zarządzania w klubach sportowych na rynkach lokalnych. Quality in Sport. 2015;1(2):7-16. eISSN 2450-3118. http://ojs.ukw.edu.pl/index.php/QiS/article/view/QUALITY%20IN%20SPORT%201%20%282%29%202015%2C%20s.%207-16   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland. Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.11.2015. Revised 20.11.2015. Accepted: 30.11.2015. Sławomir Kowalski[1] Instytut Marketingu, Wydział Zarządzania, Politechnika Częstochowska   Profesjonalizacja marketingowego zarządzania w klubach sportowych na rynkach lokalnych The professionalization of marketing management in sports club in the local market       Streszczenie Podstawowym problemem stojącym przed klubami sportowymi jest niewystarczająca wiedza w zakresie wykorzystania istniejących zasobów. Kluby sportowe o zasięgu lokalnym działają w warunkach ciągłych niedoborów finansowych, ludzkich i rzeczowych. Kwestie związane z pozyskiwaniem sponsorów, zarządzaniem szkoleniem drużyn, obiektów sportowych wymagają od ich menedżerów profesjonalnego podejścia. O ile w wyższych klasach rozgrywkowych profesjonalizm zostaje narzucony przez przepisy licencyjne, to w ligach niższych klas rozgrywkowych, lub sportach mniej popularnych, brak profesjonalizmu powoduje upadek klubu lub jego stagnację. Celem artykułu jest podanie przykładów i modelu wykorzystania wiedzy w zarządzaniu klubami sportowymi o zakresie lokalnym. Podmiotem jest tu klub RKS Raków S.A., który wdraża konkretne profesjonalizujące programy w zakresie marketingowego zarządzania klubem sportowym. Zakres przedmiotowy badań obserwacyjnych obejmuje zarządzanie wizerunkiem, relacje z interesariuszami, profesjonalne podejście do kwestii pozyskiwania sponsorów, promocji oraz organizacji widowiska sportowego. Poza tym artykuł przewiduje zarządzanie informacją i promocją na zewnątrz klubu w warunkach niedostatków finansowych z wykorzystaniem nowoczesnych rozwiązań komunikacyjnych. Artykuł powinien być pomocny w rozwiązywaniu problemów decyzyjnych klubów na szczeblu niższych klas rozgrywkowych oraz marketingowym zarządzaniu w klubach dyscyplin niszowych o lokalnym zasięgu.   Słowa kluczowe: marketing, zarządzanie, klub sportowy, zasoby.               Abstract The main problem of sports clubs is the insufficient knowledge in the use of existing resources. Local sport clubs operate in a continuous shortage of financial, human and material. Issues related to the acquisition of sponsors, training management teams, sports facilities managers require their professional approach. While in higher grades professional leagues is dictated by the rules of licensing, in the lower leagues or sports less popular, lack of professionalism causes the collapse of the club or its stagnation. This article aims to give examples and model the use of knowledge in the management of sports clubs, local scope. The subject in this article is the football club RKS Rakow Częstochowa SA, which implements specific marketing programs for managing. The scope of the observational studies include image management, stakeholder relations, professional approach to raising sponsorship, promotion and organization of sporting events. In addition, the article provides information management and promotion outside the club in terms of financial shortcomings of using modern communications solutions. The article should be helpful in solving the problems of decision-making clubs at the lower classes leagues and clubs marketing management disciplines niche for local coverage.   Key words: marketing, management, sports club, resources. [1] e-mail: sskk@op.pl